2007
DOI: 10.1007/s10773-007-9365-7
|View full text |Cite
|
Sign up to set email alerts
|

Why Unsharp Observables?

Abstract: We discuss why projection valued measures are not sufficient in the description of position and momentum of a one dimensional particle. A satisfactory solution is offered using positive operator measures. We also argue why the relevant positive operator measures, but not all, may be called unsharp observables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Carmeli and Kuzmenko [9] have Recently shown that the cosmological relativistic theory [10] predicts Λ = 1.934 × 10 −35 s −2 which is in agreement with the measurements recently obtained by the High-z Supernova Team and Supernova Cosmological Project [1]- [4]. There have been Several ansätz suggested in which the Λ term decays with time [11]- [25].…”
Section: Introductionsupporting
confidence: 83%
“…Carmeli and Kuzmenko [9] have Recently shown that the cosmological relativistic theory [10] predicts Λ = 1.934 × 10 −35 s −2 which is in agreement with the measurements recently obtained by the High-z Supernova Team and Supernova Cosmological Project [1]- [4]. There have been Several ansätz suggested in which the Λ term decays with time [11]- [25].…”
Section: Introductionsupporting
confidence: 83%
“…Hence Λ is considered to be the function of time for spatially homogeneous expanding universe. Carmeli and Kuzmenko [24] have shown that the cosmological relativistic theory predicts Λ = 1.934 × 10 −35 s −2 which is in agreement with the measurements recently obtained by the High-Z supernova team and supernova cosmological project [25]. A number of authors have studied cosmological models with time dependent cosmological term viz.…”
Section: Introductionsupporting
confidence: 81%
“…But, compatibility with other areas of physics demands that Λ should be slowly time decreasing [24]. Moreover, the currently observed small value of Λ[25] [26] suggests that it has decreased slowly from a very high value to its present nearly zero value. This type of time dependency of Λ has a similarity with that of the gravitational constant G as proposed by Dirac in his LNH [24].…”
Section: Dirac's Lnh and The Coupling Constant ξmentioning
confidence: 99%